Prywatyzacja i zysk? Przedsiębiorcy a gospodarka instytucjonalna w Mezopotamii od 3 do 1 tysiąclecia przed Chr. - Jursa, Michael (2002)
Privatisation and Profit? Entrepreneurs and Institutional Households in Mesopotamia from the Third to the First Millennium BC